Konsumsi rokok dan asupan zat gizi balita pada rumah tangga miskin - Winda Irwanti; Madarina Julia; Yayi Suryo Prabandari (Jurnal Gizi Klinik Indonesia, 2013)
Background: Eradication of poverty and starvation is still an agenda of Millennium Development Goals (MDGs) 2015 due to the serious impact of poverty and starvation to human beings. Poverty and starvation are worsened by smoking habit of the Indonesian population. Expenditures used for cigarettes may bring bad impact to the health of toddlers, including lack of nutrient intake. However, until today it is not yet precisely known how much lack of nutrient intake in toddlers caused by cigarette consumption. Objective: To identify difference in nutrient intake of energy and protein of toddlers based on the amount of cigarettes consumed in poor household at Yogyakarta Municipality.Method: The study used cross sectional design. Subject consisted of 86 toddlers of two-five years living in poor household at Yogyakarta Municipality. Cigarette consumption, mother of toddlers and all members of the family were obtained from interview. Method to assess intake was multiple 24 hours food recall within four days, whereas interview was used to assess cigarette consumption. Statistical analysis was performed by using Two Sample Independent t-test, Mann-Whitney U-test, regression, and Chi-Square.Results: As much as 77.9% of poor household had at least one smoker. There was no significant difference in intake of energy and protein of toddlers living with smokers and non smokers, though percentage of expenditure for food was significantly lower in the household with smokers. This might be due to high consumption of food with high energy density at affordable price and protein at low price. Snacks were the third most consumed by toddlers and 40% of animal protein consumed were eggs.Conclusion: There was no significant difference in intake of energy and protein of toddlers living in the poor household with smokers and those living with non smokers, but percentage of expenditure for food significantly lower in household with smokers.